Legal Framework for Consumer Protection in Digital Transactions - Ari Adi saputra; Diki pebri apriyanto; Nur Laela Hildayati (International Forum of Researchers and Lecturers, 2024)
The rapid expansion of e-commerce has introduced new complexities in consumer rights and legal protections. This article examines the legal framework for consumer protection in digital transactions, focusing on e-commerce fraud, data privacy, and contract enforcement. Through a comparative analysis, it identifies the strengths and weaknesses of existing regulations and suggests improvements to safeguard consumer rights in the digital age. The findings aim to inform policy development for enhancing consumer confidence and security in online transactions.